In vitro comparative analysis of steamed wood and other lignocellulosic substrates on ruminal fermentation and microbiota - Ito, Kazuaki; Adachi, Makoto; Scheftgen, Andrew J.; Suen, Garret; Hiyama, Ryo; Seki, Kazuto; Nakai, Shintaro; Yano, Rintaro; Nishida, Takehiro; Hanada, Masaaki; Fukuma, Naoki (Frontiers in Veterinary Science, 2026)
Lignocellulosic biomass such as wood is increasingly recognized as a promising low-opportunity-cost feed (LCF) that does not compete with human-edible food. In this study, we evaluated rumen fermentation characteristics and microbial community responses using an in vitro batch culture system with a diverse set of substrates, including steamed and untreated woods, xylo-oligosaccharides, spent mushroom substrates, and conventional feeds. Hierarchical clustering based on bacterial community composition revealed five distinct microbial clusters. Certain steamed woods and xylo-oligosaccharides formed separate clusters from untreated woods and conventional feeds, and were associated with the dominance of specific genera such as Succinivibrio and Selenomonas. These microbial shifts may reflect differences in substrate characteristics, potentially related to hemicellulose- and oligosaccharide-derived components. The results suggest that both steamed wood and xylo-oligosaccharides enhance fermentability and are associated with distinct microbial community structures under in vitro conditions. These substrates show promise as sustainable feed ingredients, and further in vivo studies are needed to evaluate their efficacy and long-term impacts on animal health and productivity.